Leadership Supervision in Improving Library Services at the Batanghari Regency Library and Archives Office - Maisarah Gusvita; Frances Alon (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2021)
This research was focused on the activity of the head of library’s supervision in improving library services at the Department of Batanghari Library and Archieve Services. This study used qualitative method by observing participants to explane, to describe, and to interprete the process of implementation the supervision that carried out by the head of the library for improving library services, based on the visitors’ satisfaction. Based on the findings and discussion, it was known that the supervision that carried out by the head of the library in improving library services at the Department of Batanghari Library and Archives Service is direct supervision (inherent) that carried out by the Head of Library Division on each type of library service to achieve the planned library objectives effectively and efficiently. The obtacle that faced by the head of the library was the library human resources were not professional yet. To overcome these obstacle, there were some efforts as follows: a) Evaluated and corrected on library service activities, b) Gift training for library human resources to improve their performance, c) Increased the discipline enforcement for library human resources, and d) Added the library collections. So, the researcher concluded that the implementation of leadership supervision carried out by the Head of the Library in improving services was inherent supervision. However, there was obtacles on the implementation of survervision, which the library human resources were not professional yet. So to overcome these problems, there were some efforts as follows: evaluated and corrected on library service activities, gift training for library human resources to improve their performance, increased the discipline enforcement for library human resources, and added the library collections to satisfy library visitors.